Analisis Pengembangan Produk Melalui Media Sosial Instagram di Donat Madu Cihanjuang pada Tahun 2023 - Bayu Asliza Fadila; Leni Cahyani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2024)
Social media has changed the way consumers and producers communicate, enabling manufacturers such as CV. Donat Madu Cihanjuang (CV. DMC) to market their products through social media marketing, such as Instagram. CV. DMC, a food company, has emphasized halal, quality and best service to their customers. This study aims to develop product branding CV. Cihanjuang Honey Donuts on Instagram. The research method used is descriptive qualitative with data collection techniques such as interviews, observation, documentation, and triangulation. The results of this study are the development of Instagram social media content in CV. The Bojongsoang Honey Donuts need to be improved again, with the first way from planning content to evaluating Instagram content.